2016
DOI: 10.3171/2016.3.spine1640
|View full text |Cite
|
Sign up to set email alerts
|

Intubation biomechanics: laryngoscope force and cervical spine motion during intubation in cadavers—effect of severe distractive-flexion injury on C3–4 motion

Abstract: OBJECTIVE With application of the forces of intubation, injured (unstable) cervical segments may move more than they normally do, which can result in spinal cord injury. The authors tested whether, during endotracheal intubation, intervertebral motion of an injured C3–4 cervical segment 1) is greater than that in the intact (stable) state and 2) differs when a high- or low-force laryngoscope is used. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Cervical spinal canal diameter is more accurately assessed by examining changes in SAC (Fig. 1) but unfortunately this outcome measure is used 1124 infrequently (Table 2) [10,27,[40][41][42][43][44]. Future research in this area needs to focus on outcomes such as vertebral canal dimension and SAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cervical spinal canal diameter is more accurately assessed by examining changes in SAC (Fig. 1) but unfortunately this outcome measure is used 1124 infrequently (Table 2) [10,27,[40][41][42][43][44]. Future research in this area needs to focus on outcomes such as vertebral canal dimension and SAC.…”
Section: Discussionmentioning
confidence: 99%
“…This is not to say that direct laryngoscopy increases the risk of spinal cord injury, as the studies that have measured SAC in this regard have shown only minor differences between different devices. In cadaveric models of C3/C4 injury and type‐2 odontoid peg fracture, there was no difference in the change in SAC with a Macintosh blade and the Airtraq videolaryngoscope [41–43]. Yet, in a cadaveric model of atlanto‐occipital instability, the King Vision aBlade did produce a smaller change in SAC compared with a Macintosh blade [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, new intubation equipment, including various types of video laryngoscopes, has been developed and introduced for the management of difficult airway. Video laryngoscopes have been reported to be more useful in managing difficult airway than standard direct laryngoscopy; however, several studies have revealed that standard direct laryngoscopy can be efficaciously and safely used with MILS techniques, even in cases of cervical spine injury 1521. However, most prospective studies have limitations in that they simulated difficult airway scenarios solely by using MILS.…”
Section: Discussionmentioning
confidence: 99%
“…MILS may be useful in reducing overall excessive cervical spine movements but has limited effect at mid cervical point of injury [14][15][16]. The movement of spine during laryngoscopy in unstable C spine do not significantly exceed the physiological values of normal intact spine movement [17,18] Patient with cervical spine injuries, the secondary neurological deterioration after laryngoscopy and intubation is very rare, with a reported incidence of less than 0.05% [19][20][21]. Gentle external laryngeal manipulation and use of bougie guided intubation are often extremely helpful in reducing the number of failed attempts [2].…”
Section: Journal Of Anesthesia and Intensive Care Medicinementioning
confidence: 99%